Opioids in the management of pain in diabetic neuropathy (2010)
Neuropathy is one of the most frequent complications of diabetes and pain, one of its more common and incapacitating symptoms. Recently there are reports of the use of opioids as an alternative of analgesic treatment. Objective: this work's objective has been to carry out a systematic review for determining the opioids power for managing pain in patients suffering from painful diabetic neuropathy. Methodology: a search and systematic selection was carried out of all clinical assays concerning the analgesic treatment of diabetic neuropathy using opioids published from January 1998 to June 2009. Randomized clinical trials compared with placebo were included which studied the analgesic effect of opioids in adults suffering from painful diabetic neuropathy; they were evaluated so that improvement of pain could be objectively classified. Results: there were nine randomized clinical trials identified. Only five were finally included: two with tramadol and three with oxycodone. The data provided by these studies did not allow to perform a meta-analysis. Conclusions: the improvement of pain in patients treated with tramadol or oxicodone was statistically significant superior when compared to placebo. It is necessary to make future clinical randomized studies to evaluate the analgesic effectiveness of opioids in painful diabetic neuropathy, including the magnitude of individual improvement, the previous definition of the percentage of improvement that is considered clinically significant and a longer time of follow-up. ©INNN, 2010.